Southern European housing policies: a legislative regulation perspective - Santos, António Duarte (2018)
Housing policy basically consists of two main areas of action: one is to plan and organize the territory and the other to promote housing, and this approach to housing provision is more focused. Governments are not the only actors in the area of economic policy but play decisive roles in the joint relationship of the efforts of the various organizations and other entities. As in other Southern European countries, Portugal is a legalistic and formalist country. This does not mean that this spirit is not necessary, but it would be more important to care less about laws and more with the analysis of their effects and impacts. The benefits of housing incorporate various quantitative and qualitative aspects, but the purchasers of this good transact the product in order to obtain the best possible return. The factors that determine the price of any capital asset and the income provided by its services are similar. The durability of housing capital implies the existence of an immense stock of supply. The quantity of housing services issued by this stock depends significantly on the owners' own investment decisions. Housing production lacks a set of inputs and its form of occupation provides a set of outputs to households. The price mechanism, as a mechanism of information transmission, is the contraposition between resources used in its relation with the outputs achieved. We intend to analyse within Portugal's housing policy its objectives and instruments and to advocate the economic and social rationality of housing policy as a strand of public policies and, at the same time, focus on housing as a sector of regulation and state intervention which is direct (State promoting) and indirect (Regulating State). The behaviour of simple creative actor and defender of the laws for the protection and development of private property is no longer the main principle characterizing its intervention in the various sectors of activity. The State may change the rules of operation of the economic activity and may even extend or reduce the scope of activity of the private sector in the various sectors. The consolidation of the State with regard to the organization of law and the exercise of power has given great importance to the rules of economic policy and the implementation of public policies. The existence of public policies is justified for several reasons, such as high levels of inefficiency in resource allocation, market structure and imperfect information. Public policies require a set of legal information designed to set the rules for public and private actors, with the aim of transferring or reallocating existing resources among the different strata of the population. With regard to the State, it is characterized by the legislative, executive and judicial powers, and in this study we are interested in its executive function as a promoter of material well-being. The sphere of this promotion results from the exchange between the legislature and the executive branch.